HUKUM PUASA BAGI PEKERJA BERAT DALAM PERSPEKTIF FIQIH - Yusya Rahman (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Fasting during Ramadan is an obligation for every Muslim who meets the requirements. However, Islamic law provides concessions (rukhsah) under certain conditions, including for heavy workers. This study aims to analyze the legal ruling of fasting for heavy workers from an Islamic jurisprudence perspective. The research uses a qualitative method with a normative approach through literature study. The results indicate that heavy workers are obligated to fast as long as they are capable. However, if the work causes severe hardship (masyaqqah) or endangers health, they are allowed to break the fast and must make up for it (qadha) on another day. Therefore, the ruling is conditional and emphasizes balance between religious obligations and the protection of life.